Improvement in mechanical and corrosion properties of cast Mg17Al12-based intermetallic alloy by modifying the microstructure with La - Yanrui Li; Shaohua Zhang; Baosheng Liu; Yinghui Wei (Journal of Materials Research and Technology)
The influence of rare earth element La addition on the microstructure evolution, mechanical properties and corrosion behavior of cast Mg17Al12-based intermetallic alloy was investigated in this article. The results indicate that the microstructure of cast Mg17Al12 alloy consists of β-Mg17Al12 matrix and a small amount of divorced eutectic structure (α-Mg + β-Mg17Al12) under non-equilibrium solidification conditions. With the increase of La content, the precipitation of La-rich dendrites and Al11La3 phases with different morphologies is promoted, and inhibits the formation of divorced eutectic structure. Compared to Mg17Al12 alloy, the ultimate compressive strength of Mg17Al12-5 wt.% La alloy increases from 378.1 MPa to 538.1 MPa and the compression strain improves from 2.8 % to 3.5 %. This synergistic increase in strength and ductility is attributed to the long needle-like Al11La3 phase blocking and deflecting the crack propagation. Additionally, the Mg17Al12-1 wt.% La alloy exhibits the best corrosion resistance, which can be ascribed to three factors: firstly, the complete inhibition of divorced eutectic structure, reducing the anode-to-cathode area ratio and micro-galvanic corrosion. Secondly, Al–La phase weakens micro-galvanic corrosion by capturing impurity elements. Moreover, La-rich dendrites facilitate the formation of a compact corrosion product layer containing La2O3 to protect the substrate effectively.